Analisis Perhitungan Poros, Pulley dan V-belt pada Sepeda Motor Honda Vario 125CC 2018 - Agung Izzulhaq Choerullah; Ratna Dewi Anjani; Farradina Choria Suci (Peneliti.net, 2022)
In the automotive world today, there are many two-wheeled vehicles with automatic transmission which have become the primary need for many people. To be able to work the vehicle, one that can support the running of the vehicle is the axle on the CVT (Continously Variable Transmission). Likewise with this study, which aims to analyze the calculation of the shaft, pulley and v-belt on the 2018 Honda Vario 125cc motorcycle in order to meet the required criteria and applicable standards. The type of research used is experimental research, data collection is carried out directly. From the calculation analysis that has been carried out, the results obtained; Shaft Diameter = 17.1 mm, Drive Pulley Diameter = 125 mm, Driven Pulley Diameter = 150 mm, Type B standard belt type with the following specifications; Width = 17 mm, Thickness = 11 mm, Groove Angle = 38°, Rubber Density = 1140 kg/cm3, Maximum Tensile Stress = 1.72 Mpa, Velocity V – Belt = 11.77 m/sec, Length V – Belt = 1071.1 mm, maximum tension V – Belt = 250.8 N, Voltage requirement V – Belt = 152.9 N, so that V – belt with Type B can be said to be safe.